2022
DOI: 10.1007/978-1-0716-1732-8_16
|View full text |Cite
|
Sign up to set email alerts
|

Methods to Study the Mitochondrial Unfolded Protein Response (UPRmt) in Caenorhabditis elegans

Abstract: The nematode Caenorhabditis elegans is a powerful model to study cellular stress responses.Due to its transparency and ease of genetic manipulation, C. elegans is especially suitable for fluorescence microscopy. As a result, studies of C. elegans using different fluorescent reporters have led to the discovery of key players of cellular stress response pathways, including the mitochondrial unfolded protein response (UPR mt ). UPR mt is a protective retrograde signaling pathway that ensures mitochondrial homeost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…For example, P. aeruginosa produces toxins that target the mitochondrial unfolded protein response (UPR MT ), 72 a transcriptional pathway that ensures proper protein folding and clearance. 73 As such, when the UPR MT is overwhelmed or disrupted, proteotoxicity can occur, leading to accelerated protein aggregation. 74 Our previous work demonstrated that P. aeruginosa and E. coli can also disrupt host proteostasis through the production of bacteria-derived protein aggregates.…”
Section: Proteotoxic Bacteria Enhance the Aggregation And Toxicity Of...mentioning
confidence: 99%
“…For example, P. aeruginosa produces toxins that target the mitochondrial unfolded protein response (UPR MT ), 72 a transcriptional pathway that ensures proper protein folding and clearance. 73 As such, when the UPR MT is overwhelmed or disrupted, proteotoxicity can occur, leading to accelerated protein aggregation. 74 Our previous work demonstrated that P. aeruginosa and E. coli can also disrupt host proteostasis through the production of bacteria-derived protein aggregates.…”
Section: Proteotoxic Bacteria Enhance the Aggregation And Toxicity Of...mentioning
confidence: 99%
“…[116] Contrary to the UPR mt induced in nematodes and flies and the cytosolic response mitochondrial stress in yeast, the heat-shock proteins (i.e., cytosolic HSP70 or mitochondrial HSPD1) are not a target of the DELE1-HRI pathway. [114,115,117] Specifically, it was shown that blockade of the OMA1-DELE1-HRI pathway upon mitochondrial stress blunts the expression of ATF4 and CHOP targets, whereas it leads to activation of heat shock protein expression. [114,115] The latter suggests that the transcriptional outcome upon mitochondrial protein import perturbations may vary depending on the trigger, and the molecular players involved.…”
Section: Mitochondrial Unfolded Protein Response (Uprmt)mentioning
confidence: 99%